RESPON PETANI TERHADAP USAHATANI KAKAO DI DESA BANJARHARJO, KECAMATAN KALIBAWANG, KABUPATEN KULON PROGO - Hartawaty, Dheny Arina; Harli, Nurlina; Haslinda, Sheila Nur (Fakultas Pertanian, Universitas Janabadra, 2023)
This study aims to evaluate the importance of cocoa plant farming in Banjarharjo Village, Kalibawang District, Kulon Progo Regency. The study was conducted for one month, from November to December 2022, using the Non Probably Sampling technique, where all cocoa farmer populations were sampled because the population was less than 30 people. Data was collected through three stages, namely observation, interview, and documentation. The data analysis technique uses the Likert scale to measure the level of farmer response to cocoa farming. The results showed that based on a number of measured indicators, the quality of cocoa farming in Banjarharjo Village can be considered high. For example,